The relative contribution of personality and cognitive abilities on leaders’ job performance, interpersonal and strategic skills - Routila, Anni (My University, 2021)
A well-conducted executive selection with valid assessment instruments can recognize high-performing employees to fit the vacant position and gain the wanted characteristics to obtain the organization’s objectives. Executive selection process applies both personality and cognitive ability tests as they complement each other and provide meaningful information. These personal characteristics are proactive drivers that direct individuals with high cognitive abilities and motivational dimensions towards leadership positions. These characteristics equally influ-ence the leader’s actions and behaviours and, ultimately, the job performance. For decades, leadership has been understood as an influencing process that requires interpersonal skills. Also, while operating in a hectic and fragmented environment, strategic skills are required to outscore the competitors and gain a competitive advantage. This research aimed to investigate to what extent the personality traits and specific cognitive abilities are related to a leader’s job performance, interpersonal and strategic skills. The personality construct is presented with a well-recognized Five Factor Model and the cognitive abilities are presented as numerical, figural, and verbal skills. 47 leaders were evaluated for job performance and interpersonal skills, out of which 27 leaders also for strategic skills. This thesis was made as a quantitative research that proceeded to answer the research questions with regression analysis. Additional findings are presented with a t-test. The results demonstrate that some of the specific cognitive abilities, equally as extraversion and conscientiousness are related with the predicted variables as follows: job performance seems to have a positive relation with the numerical skills. Interestingly, extraversion has a negative relation, and verbal test scores a positive relation with interpersonal skills. Conscientiousness seems to have a negative relationship with strategic skills, and it should be inspected as a pair with cognitive ability level.
Keywords: Executive selection, assessment, personality traits, Five Factor Model, Conscientiousness, Extraversion, Emotional stability, cognitive ability, numerical, figural, verbal, leadership skills, interpersonal skills, strategic skills